Perceived COVID-19 vaccine effectiveness, acceptance, and drivers of vaccination decision-making among the general adult population: A global survey of 20 countries - Marzo, Roy Rillera (PUBLIC LIBRARY SCIENCE, 2023)
10.1371/journal.pntd.0010103